Developing Case Method Based Course Substantial in Enriching ELT for Student of English Education Study Program - Christine Helena Natalia; Khairunnisa Br Batubara; Yuni Khairina (RIRAI Publisher, 2022)
This study aimed to develop case method-based course materials on Culture in ELT Subjects for students of the English education study program at Universitas Negeri Medan. It was conducted by using Research and Development (R&D) design. The subject of this study was 25 students in the fourth semester taken from 3 classes (C, D, and E) of the English Education study program academic year of 2021/2022. Borg, and Gall‘s research theory (1983) is used in this research, there are several procedures conducted namely gathering data and information, need analysis, designing course material, validating and evaluating new course material by the experts, and revising the course material and final product. The instruments used to collect the data were questionnaires, interviews, and expert judgment questionnaires. The data resulted from needs analysis and interviews with students and lecturers. The product of this study was English Culture on ELT course materials for the English Education Study Program based on the case method, which consists of five units. Based on the expert judgment, the whole aspects of developed materials were 81-100% and can be categorized as “very good“.